A Intervensi Kesehatan Reproduksi, Kesehatan Jiwa dan Kesehatan Anak di Indonesia - Feri Catur Yuliani; Putri Kusumawati; Aminatul Fatayati; Rizal Fajri (INVOLUSI: Jurnal Ilmu Kebidanan, 2026)
Abstract Indonesia faces significant challenges in three interrelated health domains: reproductive health (Maternal Mortality Rate/MMR of 183/100,000 live births), mental health (prevalence of mental and emotional disorders of 9.8% according to the 2018 Basic Health Research), and child health (stunting of 21.6% in 2022). These three issues are often addressed separately in the field, despite their interrelated determinants and solutions. This study aims to map the scope and characteristics of research in Indonesia addressing interventions or the linkages between reproductive, mental, and child health; identify research gaps; and formulate a future research and policy agenda. The method used was a scoping review with searches conducted on the Garuda portal, SINTA, Google Scholar, and institutional repositories of Indonesian universities. Inclusion criteria: Articles from national journals accredited with SINTA 1–4, in Indonesian or English, published between 2015–2024, covering at least two of the three domains. Exclusions included unpublished theses/dissertations, single case reports, and articles without full-text access. Of the 2,418 identified articles, 48 ​​met the inclusion criteria. Three dominant themes were identified: (1) postpartum depression and its impact on exclusive breastfeeding and infant growth and development (n=19; 39.6%); (2) the relationship between domestic violence (DV) and maternal mental health disorders and child health outcomes (n=16; 33.3%); and (3) the effectiveness of integrated home visiting programs by midwives and Posyandu cadres (n=13; 27.1%). The majority of studies were conducted on Java Island (72.9%), with cross-sectional designs predominating (52.1%). Conclusion: There is a strong relationship between the three domains documented in Indonesian research, but research outside Java has used longitudinal designs and evaluation of integrated programs is still very limited. Strengthening mental health screening in MCH services and empowering Posyandu cadres are key recommendations. Keywords: postpartum depression; DV; reproductive health; scoping review; stunting